Transnational remittances and irregularity: remitting practices of Post-Soviet labor migrants in Istanbul - Ergünöz, Mehtap. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
This thesis examines migrants’ remitting practices, which constitute a much neglected issue in the literature, with the case of Post-Soviet irregular labor migrants in Istanbul based on the data collected through semi-structured interviews with the migrants and discussions with other actors involved in the remitting processes. The thesis sets off from that these migrants invent new informal remitting practices to send money to kin left behind as there are limitations on the possibilities of transferring remittances just like many other daily constraints they have to face due to their legal status in the country and that these practices are not only determined by transnationality and irregularity but also offer a new alternative micro field for the examination of them. By taking the relationship between irregularity and informality as not an automatic one, it scrutinizes the emergence of these informal practices at the juncture of transnationality and irregularity and evaluates them as an informal and also an integral part of the massive migration industry. In addition, regarding the attempts of states and international organizations at attracting the informal remittances of irregular migrants to formal channels, the thesis underlines that as both irregularity and informality emerge under the limitations on the everyday lives of migrants an effective solution for the issue of channelling informal remittances to formal channels would be the abolishment of all limitations on migrants by regularizing their status.
Keywords: Emigration and immigration -- Economic aspects -- Case studies.